Saj’ Murashsha’ dalam Surah Al-Waqi’ah: (Studi Analisis Balaghah) - Raudhatul Jannah; Ariza Amalia; Nabila Nashfati; Harun Al-Rasyid (Reflection : Islamic Education Journal, 2025)
This article examines saj’ in the science of badi’ and provides examples of the use of saj’ murashsha’ in Surah Al-Waqi’ah. Saj’ is a part of muhassinat al-lafdziyah that specifically discusses the similarity of the final letters in two or more fashilahs. Saj’ is divided into three types: saj’ mutharraf, saj’ murashsha’, and saj’ mutawazi. This research employs a qualitative approach through library study. Based on the analysis conducted by the researcher, there are six instances of saj’ murashsha’ found in Surah Al-Waqi’ah.